ANALISIS KESIAPAN PENERAPAN PEMBELAJARAN E-LEARNING MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 KUMELEMBUAI - Omega Tesalonika Wagei; Hermon Maurits Karwur; Muhamad Isa Ramadhan (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The era of technology-based information encourages the world of education to take advantage of the process of learning activities. The best thing during the Covid-19 pandemic, the learning process is transforming from face-to-face learning in class to online-based. However, school factors, management, students, culture, and others affect the learning process, in the sense that it needs readiness in its implementation. The purpose of the study was to analyze the readiness of the application of the e-learning learning model in the subject of Geography. The research method used in this study is a qualitative research method with a descriptive approach. The focus and sub-focus of this research is the readiness to apply online learning in the subject of Geography. The results showed that the components in the application of e-learning, namely the principal, subject teachers were ready to carry out the learning. This is indicated by the fulfillment of readiness indicators, including schools that prepare supporting facilities and infrastructure, teachers who undergo information technology training and can apply them in subjects. Indicators that are not met are students who have difficulty accessing internet services, and getting internet credit or study quotas, but students have been able to adapt to e-learning learning activities. The fulfillment of most of the indicators for the implementation of e-learning, shows that SMA Negeri 1 Kumelembuai, South Minahasa Regency is quite ready to implement e-learning in geography subjects.